Expression of DKK3 in chronic glomerulonephritis tissues and its induction of migration of glomerular podocytes - XU Wei-jia; LI Tao; FEI Pei; CHENG Peng; ZHU Xiao-wen (Linchuang shenzangbing zazhi)
Objective To investigate the expression of DKK3 in chronic glomerulonephritis tissues,and to discuss the roles of DKK3 in development and progression of chronic glomerulonephritis.Methods As the study object,20 cases of normal human nephridial tissues,80 cases of human chronic glomerulonephritis tissues were collected.With real-time quantitative PCR and Western blotting,relative expression of DKK3 in these normal human nephridial tissues and human chronic glomerulonephritis ones were examined..With Pearson correlation test,the correlation of DDK3 with expression of β-catenin in the human chronic glomerulonephritis tissues were investigated.Glomerular podocyte line MPC5 was selected to conduct over-expression of the DDK3 gene,and through Transwell migration assay effects of cell migration and invasion were explored in the test group and the control group.With Western blotting,induction of DDK3 on glomerular podocyte migration and invasion was analyzed.Results Compared to the normal nephridial tissues,expression of DKK3 was upregulated in the human chronic glomerulonephritis tissues(P<0.01),and meanwhile exhibited positive correlation with expression of β-catenin and involved in progression of chronic glomerulonephritis(P=0.0002,r~2=0.1651).Transwell migration and invasion assays showed that over-expression of DKK3 in the cell line MPC5 significantly promoted migration and invasion of podocytes(P<0.001).Furthermore,Western blotting assay indicated that over-expression of DDK3 upregulated expressions of some proteins including Vimentin,N-cadherin,MMP7 and β-catenin,and down-regulated expression of E-cadherin.Conclusions Up-regulation of DKK3 in human chronic glomerulonephritis tissues suggests that DDK3 may be a key regulator to involve in development and progression of chronic glomerulonephritis.